Kaleidoscopical configurations in groups - I. V. Protasov; S. Slobodianiuk (Математичні Студії, 2011)
A subset A of a group G is called a kaleidoscopical configuration if there exists a surjective coloring χ:X→κ such that the restriction χ|gA is a bijection for each g∈G . We give two topological constructions of kaleidoscopical configurations and show that each infinite subset of an Abelian group contains an infinite kaleidoscopical configuration.